The Creation of God in The Mind of Mankind: A Spiritual Need or Hiding in A Cave - Gurevitz, Michael (European Journal of Applied Sciences, 2023)
Half of the world population believes in the existence of a cosmic superpower, the creator of the world often named ‘king of the kings’ or God.